2003
DOI: 10.1007/s11325-003-0053-4
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide (NO) and Obstructive Sleep Apnea (OSA)

Abstract: Nitric oxide (NO) and obstructive sleep apnea are inseparable. Obstructive sleep apnea could be described as the intermittent failure to transport the full complement of nasal NO to the lung with each breath. There NO matches perfusion to ventilation. NO is utilized by the efferent pathways that control the unequal, inspiratory battle between the pharyngeal dilators and the closing negative pressures induced by the thoracic musculature. Recurrent cortical arousals are a major short-term complication, and the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 77 publications
0
45
0
4
Order By: Relevance
“…18,19 Initially, OSAS was examined as one of the causes underlying intermittent failure to transport the full complement of nasal nitric oxide (NO) to the lung with each breath. 20 Although further study should be conducted to investigate the relationship between NO and OSAS, the impairment of the vasoprotective function of NO as a result of respiratory disturbances during nighttime sleep may explain the association between OSAS and ED. 21 Testosterone has been proposed as another linking factor between ED and hypoxia, though it is controversial.…”
Section: Erectile Dysfunction In Osas H-w Shin Et Almentioning
confidence: 99%
“…18,19 Initially, OSAS was examined as one of the causes underlying intermittent failure to transport the full complement of nasal nitric oxide (NO) to the lung with each breath. 20 Although further study should be conducted to investigate the relationship between NO and OSAS, the impairment of the vasoprotective function of NO as a result of respiratory disturbances during nighttime sleep may explain the association between OSAS and ED. 21 Testosterone has been proposed as another linking factor between ED and hypoxia, though it is controversial.…”
Section: Erectile Dysfunction In Osas H-w Shin Et Almentioning
confidence: 99%
“…Nitric oxide also suppresses the smooth muscle proliferation and induces apoptosis of these cells, providing beneficial effects on vascular remodeling [39]. Thus, long-term complications of OSA including systemic hypertension, pulmonary hypertension, myocardial infarction, and stroke might be influenced by dysregulated nitric oxide [40]. Experiments by Kato et al [41] showed that patients with OSA had a blunted vasodilation in response to acetylcholine, but not in response to sodium nitroprusside or verapamil, indicating that OSA patients have impaired resistance-vessel endothelium-dependent vasodilation, but the smooth muscle cell response itself is normal.…”
Section: Evidence For Altered Nitric Oxide Production In Osa Patientsmentioning
confidence: 99%
“…[7][8][9] NO and obstructive apnea are inseparable conditions. 10 Thus, the impairment of NO vasoprotective function may explain the association between OSAS and ED and may also indicate optimal therapeutic management.…”
Section: Introductionmentioning
confidence: 99%